Video Project and Social Media: A Collaboration for Shaping Learner’s Speaking Ability - Sari, Maria Puspa (ELT Worldwide: Journal of English Language Teaching, 2024)
Over the past two decades, technology has been widely harnessed in English language teaching for the sake of learners’ quality. This research was conducted to figure out if there was significant difference of the speaking achievement between students who uploaded their video projects online and those who did not. This study was an experimental study harnessing video project combined with social media, Instagram, as the treatment. Two groups of mining students consisting 52 participants were selected randomly and categorized into experimental and control group. Mining students were selected in this study as the college, Akamigas Polytechnic of Palembang, where this study conducted demands the learners to speak English in the campus. The results from Wilcoxon test revealed that posting video online showed a statistically significant change in the speaking performance of the experimental group (Z = -4.207, p = 0.000). Finally, significant difference in the speaking skill was also found between the two groups shown by the result of Mann Whitney Test where the sig. value was 0.029 lower than 0.05. In conclusion, this study revealed that video project was absolutely effective to boost learners’ speaking skill. However, posting them on Instagram is more effective and meaningful